Backgrounds of Early Christianity - Ferguson, Everett (William B. Eerdmans Publising Company, 2003)
Having long served as a standard introduction to the world of the early church, Everett Ferguson's Backgrounds of Early Christianity has been expanded and updated in this third edition. The book explores and unpacks the Roman, Greek, and Jewish political, social, religious, and philosophical backgrounds necessary for a good historical understanding of the New Testament and the early church. New to this edition are revisions of Ferguson's original material, updated bibliographies, and fresh discussions of first-century social life, of Gnosticism, and of the Dead Sea Scrolls and other Jewish literature.